Migration, Fears and the Media in the Presidential Election in Chile 2017 - Dammert-Guardia, L (UNIV ICESI, 2020)
Migration has been defined as the threatening other in Latin America; Chile is no exception. Based on the conceptualization of the imagined community, this article analyzes the importance and characteristics of press media coverage on migration and punitive populism in the framework of the Presidential election of 2017 in Chile. A random sample of all the informative pieces of the two main newspapers throughout 2017 was analyzed. Migration has become a topic of national debate. The media show a political discourse focused on punitive populism, the unnecessary generalization of stigmatizing images, and the consolidation of a metaphor that links migration with danger, mainly criminality. The more chronic-oriented than analysis-oriented characteristic of the coverage makes it possible to emphasize in the threatening and politically profitable images. Possibly trying to protect that community that the political discourse constantly highlights.